PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA MATERI PERAN EKONOMI MASYARAKAT KELAS V SDN SIDOSARI - Kana Rosida; Titi Anjarini; Nurhidayati (STKIP Subang, 2024)
This study aims to 1) Describe the implementation of the Teams Games Tournament (TGT) learning model, 2) Increase students' learning engagement through the application of the Teams Games Tournament (TGT) learning model, and 3) Improve students' learning outcomes by applying the Teams Games Tournament (TGT) learning model. This research employs a Classroom Action Research (CAR) methodology, consisting of two cycles, with each cycle comprising two sessions. The subjects of the study are 20 fifth-grade students at SDN Sidosari, consisting of 7 boys and 13 girls. Data collection methods include interviews, observations, and documentation. The Teams Games Tournament (TGT) learning model is implemented through five stages: 1) Class Presentation, 2) Group Study, 3) Games, 4) Tournaments, and 5) Group Rewards.The observation results indicate that the application of the Teams Games Tournament (TGT) model is highly suitable for Elementary Schools. Student engagement in learning increased from 49% in the pre-cycle stage to 61% in the first cycle, and then significantly to 79% in the second cycle. This data shows that the learning engagement of fifth-grade students has reached the success indicators and is categorized as active. Additionally, students' learning outcomes improved from 61% in the pre-cycle, to 68% in the first cycle, and reached 87% in the second cycle, exceeding the class achievement indicator of ≥75. Based on these results, the application of the Teams Games Tournament (TGT) model is proven effective in increasing student engagement and learning outcomes, making this model a viable strategy for enhancing student engagement and learning outcomes in Elementary Schools.